اتجاهات معلمي صعوبات التعلم نحو توظيف السبورة التفاعلية في العملية التعليمية ومعوقات استخدامها بسلطنة عمان = Attitudes of teachers of learning disabilities towards the use of the interactive whiteboard in the educational process and the obstacles to its use in Sultanate of Oman - Ahmed Nasir Al Rahby, Amal; Sahrir, Muhammad Sabri (National Research Center, Palestine, 2022)
This study aims to know the attitudes of teachers of learning disabilities program towards using the interactive whiteboard, and to know the advantages and obstacles of using the interactive whiteboard in teaching students with learning disabilities. The researcher has followed scientific methodologies to do her research. Through thedescriptive approach, the researcher used a questionnaire on (106) teachers of learning disabilities to study their attitudes towards the interactive board, the advantages of using it on students with learning disabilities, and the difficulties teachers face while using the interactive board. The study concluded a set of results, the most important of which are:The overall average of the teachers' attitude toward on the trends scale was (4.13) and thus Teachers of learning disabilities have a highly positive attitude toward using the interactive whiteboard, that the interactive whiteboard encourages the teacher to use teaching aids with visual, kinesthetic and auditory approaches with ease, support for the spread of the interactive whiteboard in all schools, and that the use of the interactive whiteboard increases teachers’ computer skills-It suits all levels and curricula, teachers feel confident when using the interactive whiteboard. And that the total average of teachers’ evaluation of the positives of using the interactive whiteboard in teaching students with learning disabilities was (4,24), which is very highly positive, and contributed to increasing their learning speed, interaction, and motivation towards learning.Teachers of learning disabilities face a number of difficulties that have greatly affected their use of the interactive whiteboard,The average teacher rating of these obstacles was (4.10), including: the slow internet needed to use the interactive whiteboard, the lack of manuals for the teacher explaining how to use the interactive whiteboard, and the lack of maintenance needed for the interactive whiteboard in the event of a technical failure. At the end, the researcher concluded with a set of recommendations,including: providing more interactive whiteboard devices in the classrooms in a way that allows teachers and students to make optimal use of this technology, the need to implement training courses and employ the necessary learning resources to increase the skills of students and teachers and raise their competencies in the use of the interactive whiteboard, interest in providing Internet service for all classrooms in schools.